Health care provision for refugees in Germany - one-year evaluation of an outpatient clinic in an urban emergency accommodation - Borgschulte, Hannah Sophia; Neuhann, Florian (BMC health services research, 2018)
In 2015, Germany recorded the highest rates of refugees since the early 1990s. Access to medical care is a legally regulated fundamental element of aid for refugees. In practice, there are several hurdles such as language barriers and legal regulations. In response to the massively increased need, special outpatient services for refugees were started in several German cities. In Cologne, an outpatient clinic (OPD) was established in the largest emergency accommodation centre for refugees supported by the Cologne municipality and operated by the German Red Cross and physicians from the Association of Statutory Health Insurance Physicians. This study reports experiences of the first year of the OPD regarding structure, processes and utilization.